בין פדיון לפדות: על שירתם של שלונסקי ואלתרמן כתגובה לרטוריקה המשיחית בשירה העברית - גרינוולד, רועי (מכאן, 2014)
The article examines the rise of the neo-Symbolist school in Hebrew literature during the 1930s. It argues that the poetry of the leading figures of the school, Avraham Shlonsky and Nathan Alterman, should be understood against the backdrop of the abundant use of messianic vocabulary in the poetry of the Third Aliyah (including by Shlonsky himself) at the beginning of the 1920s. Through close reading of the economic metaphors in the poetry of Shlonsky and Alterman, the article shows how the neo-Symbolist poetics was affected by inflationary conditions that befell the representations of the Zionist endeavor. Drawing on the theories of Georg Simmel (especially in Philosophy of Money) and situating the poetry within the context of the world financial crisis between the two World Wars, the article demonstrates how the relationship between the written word and material history in the poetry of neo-Symbolists in Eretz Israel seemed to mirror the relationship between the financial markets and the real economy – and themselves, therefore, as speculators in ideas that had lost their grounding.